Cu-[Ni, Co]-Si SYSTEM COPPER ALLOY PLATE MATERIAL, ENERGIZATION COMPONENT, AND HEAT DISSIPATION COMPONENT
The Cu-[Ni,Co]-Si copper alloy with controlled S content and S-containing phase particles, combined with optimized manufacturing processes, addresses the challenge of improving press punching and bending workability, achieving a balance of strength, fatigue, and conductivity.
Patent Information
- Application Number
- JP2023162911
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2043-09-26
AI Technical Summary
Existing Cu-[Ni,Co]-Si copper alloys face challenges in achieving improved press punching performance while maintaining good bending workability, particularly as parts become smaller and manufacturing processes require higher precision to reduce mold wear.
The development of a Cu-[Ni,Co]-Si copper alloy with a specific chemical composition that includes 0.005-0.10% S, controlled number density of S-containing phase particles, and optimized manufacturing processes such as casting, hot rolling, cold rolling, solution treatment, and aging treatment to enhance press punching and bending workability.
This approach results in a copper alloy sheet material with improved press punching performance, maintained bending workability, and a moderate strength level (500 MPa or more and less than 900 MPa), along with excellent fatigue properties and conductivity.
Smart Images

Figure 2025053843000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a Cu-[Ni,Co]-Si based copper alloy sheet material having improved press punching property and bending property, and to a current-carrying part and a heat-dissipating part using the Cu-[Ni,Co]-Si based copper alloy sheet material as a material. Here, the Cu-[Ni,Co]-Si based copper alloy is a general term for Cu-Ni-Si based copper alloys, Cu-Co-Si based copper alloys, and Cu-Ni-Co-Si based copper alloys. [Background technology]
[0002] Among copper alloys, Cu-[Ni,Co]-Si copper alloys have a relatively good balance between strength and electrical conductivity, and are useful for current-carrying parts such as connectors and lead frames, and heat-dissipating parts for electronic devices. When processing copper alloy sheets into current-carrying parts and heat-dissipating parts, they generally go through the processes of press punching and bending. Various methods have been investigated to improve the press punching and bending workability of Cu-[Ni,Co]-Si copper alloys.
[0003] Patent Document 1 discloses a technique for improving the strength and bending workability of a Cu-[Ni,Co]-Si based copper alloy by optimizing the texture. It does not disclose a material containing S, and does not provide any specific teaching regarding the improvement of press punchability. Patent Document 2 discloses a technique for improving press-punchability in a Cu-[Ni,Co]-Si-based copper alloy by increasing the number density of precipitates near the surface layer of the sheet compared to the center. In this document, a material with little sagging and burrs on the cut surface is evaluated as having good press-punchability (paragraph 0091). No material containing S is shown. Patent Document 3 discloses a technique for improving the strength and bending workability of a Cu-[Ni,Co]-Si based copper alloy by controlling the cooling rate during solution treatment. It does not disclose any material containing S, and does not provide any specific teaching regarding the improvement of press punchability.
[0004] Patent Document 4 discloses a technique for improving solder wettability and spring properties by optimizing the size and number density of precipitates in a Cu-[Ni,Co]-Si based copper alloy using a three-stage aging treatment process. It does not disclose any material containing S, and does not provide any particular teaching regarding improvements in press punching properties or bending workability. Patent Document 5 discloses a technique for improving the strength and press-punchability of a Cu-[Ni,Co]-Si-based copper alloy by adding S and controlling the number density of Mg-S-based particles. There is no specific teaching about improving bending workability. Patent Document 6 discloses a technique for improving bending workability and stress relaxation properties in a Cu-[Ni,Co]-Si based copper alloy by optimizing the crystal grain size and the degree of softening before and after preliminary annealing. It does not disclose a material containing S, and does not provide any particular teaching regarding the improvement of press punchability. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP2011-117034A [Patent Document 2] JP 2012-224922 A [Patent Document 3] JP 2015-187308 A [Patent Document 4] JP 2011-214088 A [Patent Document 5] JP 2021-134376 A [Patent Document 6] JP 2013-95977 A Summary of the Invention [Problem to be solved by the invention]
[0006] Recently, miniaturization, narrowing of pitch, and mass production of parts have progressed, and the importance of suppressing wear of dies used in bending and the like has increased. According to the technology of Patent Document 5, in a Cu-[Ni,Co]-Si-based copper alloy, it has become possible to significantly improve strength and press punchability by making the structure state in which Mg-S-based inclusions are dispersed. That is, it has been shown that the addition of S is extremely effective in improving press punchability. However, when the press punchability is improved by adding S, bending workability may decrease, and further improvement has been desired. In addition, although the technology of Patent Document 5 achieves a very high strength level, there are many applications such as current-carrying parts and heat-dissipating parts that do not require such high strength. Excessive high strength increases the manufacturing load of parts, which causes a lack of proper balance between required characteristics and manufacturing costs.
[0007] The present invention aims to provide a technology for improving press-punching properties while maintaining good bending workability in Cu-[Ni,Co]-Si-based copper alloys by utilizing a method of adding S, which can provide a plate material with a highly versatile medium strength level (tensile strength in the rolling direction of 500 MPa or more and less than 900 MPa). [Means for solving the problem]
[0008] In order to achieve the above object, the present specification discloses the following invention.
[0009] [1] The chemical composition, by mass%, is: total of Ni and Co: 1.00-3.60%, Si: 0.20-2.00%, S: 0.005-0.10%, Ag: 0-1.00%, Al: 0-3.00%, B: 0-0.50%, Cr: 0-1.00%, Fe: 0-3.00%, Mg: 0-1.50%, Mn: 0-1.50%, P: 0-0.50%, Sn: 0-3.00%, Ti: 0-1.00%, Zn: 0-3.00%, Zr: 0-1.00%, the balance being Cu and unavoidable impurities, and the number density of S-containing phase particles with a major axis of 2.0 μm or more and less than 5.0 μm is 50 particles / mm 2 or more, and the number density of S-containing phase particles with a major axis of 5.0 μm or more is 50 particles / mm 2 The copper alloy sheet material is as follows: [2] The copper alloy sheet material according to the above [1], wherein the total content of Ag, Al, B, Cr, Fe, Mg, Mn, P, Sn, Ti, Zn, and Zr is 4.00 mass% or less. [3] The copper alloy sheet material according to the above [1] or [2], wherein the Ni content is 0.80 to 3.50 mass %. [4] The copper alloy sheet material according to any one of the above [1] to [3], having a tensile strength in the rolling direction of 500 MPa or more and less than 900 MPa. [5] The copper alloy sheet material according to any one of the above [1] to [4], having an electrical conductivity of 40% IACS or more. [6] The copper alloy sheet material according to any one of the above [1] to [5], wherein a ratio (MBR / t) of the minimum bending radius (MBR) at which cracks do not occur to the sheet thickness (t) in a 90°W bending test in BW in accordance with the Japan Copper and Brass Association technical standard JCBA T307:2007 is 2.5 or less. [7] In a test using a test piece with its longitudinal direction perpendicular to the rolling direction, the fatigue limit at a load stress of 300 MPa was 10 6 The copper alloy sheet material according to any one of the above [1] to [6], wherein the copper alloy sheet material has a temperature of 10000 sintering cycles or more. [8] A casting process in which a molten copper alloy having the chemical composition described in [1] above at 1180 to 1420 ° C is poured into a mold, solidified, and then cooled from 1100 ° C to 600 ° C at an average cooling rate of 65 ° C / s or more to obtain a cast piece; a hot rolling process in which the slab is heated to 880 to 1100°C and then hot-rolled to a total rolling ratio of 85% or more to obtain a hot-rolled sheet; A first intermediate cold rolling process in which the hot-rolled sheet is subjected to cold rolling at a total rolling reduction rate of 60% or more; an intermediate annealing step in which the plate material obtained in the first intermediate cold rolling step is subjected to a heat treatment at 430 to 620 ° C. for 0.1 to 20 hours; A final intermediate cold rolling process in which the plate material obtained in the intermediate annealing process is subjected to cold rolling at a total rolling reduction rate of 75% or more; a solution treatment process in which the plate material obtained in the final intermediate cold rolling process is subjected to a heat treatment at 800 to 1020 ° C. for 10 to 600 seconds; An aging treatment step of subjecting the sheet material obtained in the solution treatment step to heat treatment by holding it at 400 to 550 °C for 1 to 24 hours, A finish cold rolling step of subjecting the sheet material obtained in the aging treatment step to cold rolling with a total rolling reduction rate of 10 to 80%, A finish heat treatment step of subjecting the sheet material obtained in the finish cold rolling step to heat treatment by holding it at 140 to 500 °C for 5 to 3600 seconds, A method for manufacturing a copper alloy sheet material according to any one of [1] to [7] above, including [9] In the chemical composition of the copper alloy molten metal poured into the mold in the casting step, the total content of Ag, Al, B, Cr, Fe, Mg, Mn, P, Sn, Ti, Zn, Zr is 4.00% by mass or less. The method for manufacturing a copper alloy sheet material according to [8] above.
[10] In the chemical composition of the copper alloy molten metal poured into the mold in the casting step, the Ni content is 0.80 to 3.50% by mass. The method for manufacturing a copper alloy sheet material according to [8] or [9] above.
[11] An electrical component using the copper alloy sheet material according to any one of [1] to [7] above as a material.
[12] A heat dissipation component using the copper alloy sheet material according to any one of [1] to [7] above as a material.
[0010] In this specification, "sheet material" means a sheet-shaped metal material. A thin sheet-shaped metal material may also be called "foil", and such "foil" is also included in the "sheet material" referred to here. A long sheet-shaped metal material wound in a coil shape is also included in the "sheet material". Also, in this specification, the thickness of the sheet-shaped metal material is called "sheet thickness". Also, "sheet surface" means a surface perpendicular to the sheet thickness direction of the sheet material. The sheet surface may also be called "rolling surface". In this specification, the notation "n1~n2" indicating a numerical range means "n1 or more and n2 or less". Here, n1 and n2 are numerical values satisfying n1 < n2.
[0011] In this specification, "press punchability" is an index evaluated by the area ratio of the "shear surface" in the cut surface (cut edge) when punching is performed with a press die at an appropriate clearance. In order to stabilize the quality in the punching process, it is important to extend the die life. The cut surface of a metal plate formed by press punching usually has a shear surface and a fracture surface (see Figure 1). When punching is performed with an appropriate clearance, the smaller the proportion of the shear surface is in a material, the more advantageous it is for extending the die life. Therefore, in this specification, it is said that the press punchability is better for a material that has a smaller proportion of the shear surface in the cut surface when punched under the same conditions.
[0012] The "major axis" is the maximum possible length of a line segment (which must not extend outside the particle) connecting two points on the contour of a particle on the image plane.
[0013] The total rolling ratio (%) in a certain rolling process is determined by the following formula (1). Total rolling ratio (%) = 100 × (h0-h1) / h0…(1) h0: Plate thickness before the first pass of the rolling process (mm) h1: Plate thickness at the end of the final rolling pass of the rolling process (mm) Effect of the Invention
[0014] According to the present invention, a Cu-[Ni,Co]-Si based copper alloy sheet material having improved press punching property while maintaining good bending workability has been realized, and a sheet material having a medium strength level and high versatility has been realized. [Brief description of the drawings]
[0015] [Figure 1] FIG. 4 is a diagram showing a schematic shape of a cut edge of a metal plate after being punched by a press. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] [Chemical composition] Hereinafter, "%" regarding the composition of a component means "% by mass" unless otherwise specified.
[0017] The present invention is directed to a Cu (copper)-[Ni,Co]-Si based copper alloy containing at least one of Ni (nickel) and Co (cobalt) and also containing Si (silicon). Ni, Co and Si form precipitates mainly composed of (Ni,Co)2Si, which contribute to improving strength and electrical conductivity. They also contribute to improving fatigue properties. The total content of Ni and Co can be set in the range of 1.00 to 3.60%, and the Si content can be set in the range of 0.20 to 2.00%. In this range, an appropriate strength level, which will be described later, can be obtained. It is more preferable to contain Ni in the range of 0.80 to 3.50%.
[0018] S (sulfur) is an important component element in the present invention. In general, in copper alloys, S is often treated as an impurity from the viewpoint of suppressing deterioration of hot workability and deterioration of material properties. In the manufacturing process of copper alloys, the S content is usually reduced by methods such as degreasing of raw materials and floating separation in molten metal. However, in the present invention, the S-containing phase particles are dispersed in the material to improve the press punchability. Therefore, a predetermined amount of S is contained in the copper alloy as a source of generation of S-containing phase particles. As a result of various studies, it is effective to control the S content in the range of S: 0.005 to 0.10%. If the S content is too low, the amount of S-containing phase particles generated becomes insufficient, and the effect of improving the press punchability cannot be obtained. The S content is more preferably 0.006% or more, and even more preferably 0.008% or more. If the S content is excessive, the hot workability becomes poor and cracks are easily generated during hot rolling. In addition, from the viewpoint of obtaining good bending workability, it is effective to have a low S content. The S content is preferably adjusted to a range of 0.05% or less, and more preferably 0.03% or less.
[0019] Other optional elements may include one or more of Ag (silver), Al (aluminum), B (boron), Cr (chromium), Fe (iron), Mg (magnesium), Mn (manganese), P (phosphorus), Sn (tin), Ti (titanium), Zn (zinc), and Zr (zirconium). The contents of these optional elements may be set within the ranges of Ag: 0-1.00%, Al: 0-3.00%, B: 0-0.50%, Cr: 0-1.00%, Fe: 0-3.00%, Mg: 0-1.50%, Mn: 0-1.50%, P: 0-0.50%, Sn: 0-3.00%, Ti: 0-1.00%, Zn: 0-3.00%, and Zr: 0-1.00%. The total content of these optional elements is preferably 4.00 mass % or less from the viewpoint of a good balance between press-punching property, bending property, strength, and fatigue properties.
[0020] Considering economy and manufacturability, the contents of the above optional elements are more preferably in the ranges of Ag: 0-0.40%, Al: 0-2.00%, B: 0-0.20%, Cr: 0-0.70%, Fe: 0-2.00%, Mg: 0-1.20%, Mn: 0-1.20%, P: 0-0.20%, Sn: 0-2.00%, Ti: 0-0.80%, Zn: 0-2.00%, and Zr: 0-0.40%. In this case, the total of these elements is more preferably 2.50 mass% or less.
[0021] The contents of the above optional elements may be controlled within the ranges of Ag: 0-0.20%, Al: 0-1.00%, B: 0-0.10%, Cr: 0-0.30%, Fe: 0-1.00%, Mg: 0-0.60%, Mn: 0-0.60%, P: 0-0.10%, Sn: 0-1.00%, Ti: 0-0.40%, Zn: 0-1.00%, and Zr: 0-0.20%. In this case, the total content of these elements may be controlled to 1.20 mass% or less.
[0022] The inclusion of elements other than those mentioned above is permitted within a range that does not impair the object of the present invention (improving press-punching property while maintaining good bending workability). Specifically, the total content of elements other than Ni, Co, Si, S, Ag, Al, B, Cr, Fe, Mg, Mn, P, Sn, Ti, Zn, Zr, and Cu (hereinafter, sometimes referred to as "unspecified elements") is preferably 0.50% or less, and may be controlled to 0.10% or less. The content of unspecified elements can be grasped by quantifying substantially all elements that may be contained in the copper alloy sheet, for example, by the following analytical method.
[0023] (Example of quantitative determination method for alloying elements) O (oxygen) and N (nitrogen) are quantified using an oxygen / nitrogen / hydrogen analyzer (e.g., ONH-836, manufactured by LECO), H (hydrogen) is quantified using a hydrogen analyzer (e.g., EMGA-921, manufactured by Horiba, Ltd.), C (carbon) and S (sulfur) are quantified using a carbon-sulfur analyzer (e.g., CS844, manufactured by LECO), elements of the second to sixth periods (excluding C, N, O, group 17 elements, group 18 elements, Tc (technetium), Po (polonium), and Pm (promethium)) are quantified using ICP-MS (e.g., 7900, manufactured by Agilent), and F (fluorine), Cl (chlorine), and Br (bromine) are quantified using a combustion-ion chromatography apparatus (e.g., DIONEX ICS-1600, manufactured by Thermo Scientific).
[0024] Regarding the chemical composition of the copper alloy sheet material according to the present invention, it can be specified as "consisting of one or more of Ni and Co, Si, S, the optional elements listed above (including cases where the total is 0% by mass), the balance being Cu and unavoidable impurities," or it can be specified as "consisting of one or more of Ni and Co, Si, S, the optional elements listed above (including cases where the total is 0% by mass), the unspecified elements listed above (including cases where the total is 0%), the balance being Cu."
[0025] [S-containing phase particles] In this specification, the term "S-containing phase particles" refers to second phase particles present in a copper alloy, in which the presence of S is observed by EDX (energy dispersive X-ray fluorescence analysis). The particles include particles of S alone and compound particles containing S. It is believed that the compound particles are mainly composed of sulfides with metals that easily bond with S, such as MgS, MnS, and CrS, depending on the alloy elements contained.
[0026] According to the research of the inventors, it was found that S-containing phase particles having a particle diameter of 2.0 μm or more and less than 5.0 μm in terms of the long axis, as observed in the observation of the sample surface parallel to the sheet surface, are extremely effective in improving press punching properties. S-containing phase particles having a particle diameter of 2.0 μm or more and less than 5.0 μm in terms of the long axis are considered to be the starting points of fracture during press processing, which is considered to contribute to reducing the proportion of sheared surfaces. On the other hand, coarse S-containing phase particles having a particle diameter of 5.0 μm or more in terms of the long axis are a factor in deteriorating bending workability and fatigue properties. Such coarse S particles are likely to be the starting points of cracks during bending processing.
[0027] As a result of detailed investigation, the number density of S-containing phase particles with a major axis of 2.0 μm or more and less than 5.0 μm was set to 50 particles / mm 2 It was found that by setting the above, the proportion of sheared surfaces in the cut edge formed when shear processing (press punching) is performed with an appropriate clearance is significantly reduced. This extends the life of the press die, reduces defects in the punching die in mass production, and stabilizes the quality of parts. In other words, press punching properties are significantly improved. Increasing the number density of S-containing phase particles with a major axis of 2.0 μm or more and less than 5.0 μm is difficult in terms of manufacturing. The number density of the S-containing phase particles is usually 1500 particles / mm 2 The number of pieces per mm is 70 to 1200. 2 On the other hand, the number density of S-containing phase particles having a major axis of 5.0 μm or more may be controlled within the range of 50 particles / mm 2 By suppressing the above, good bending workability is ensured and at the same time, fatigue properties are also improved. Such a structural state can be realized by following the above-mentioned chemical composition and the manufacturing method described later.
[0028] (Method for measuring the number density of S-containing phase particles) The surface of the copper alloy sheet material is polished to obtain a sample surface for EDX measurement. The sample surface is observed by a FE-SEM (field emission scanning electron microscope) equipped with an EDX device, and a measurement area of, for example, 300 μm × 400 μm is randomly determined. In the FE-SEM observation, a JSM-7200F manufactured by JEOL Ltd. is used to obtain a secondary electron image under the conditions of an acceleration voltage of 15 kV, a current of 13 A, and a WD (working distance) of 10 mm. For this secondary electron image, EDX point analysis is performed on particles with a major axis of 1 μm or more to determine whether these particles are S-containing phase particles. The major axis is the length of the longest line segment that can be drawn within the particle (limited to those that do not go outside the particle outline). In the EDX point analysis, particles with an S analysis concentration of 0.5 mass% or more are treated as S-containing phase particles. For the secondary electron image obtained, the number of S-containing phase particles with a major axis of 2.0 μm or more and less than 5.0 μm, and the number of S-containing phase particles with a major axis of 5.0 μm or more that are present within the measurement area are counted. For particles that are partially cut off by the boundary of the measurement area, the boundary part is considered to be part of the particle's outline, and the major axis is measured for the particle part that is within the measurement area. This operation is performed for multiple non-overlapping measurement areas, and the total number of S-containing phase particles with a major axis of 2.0 μm or more and less than 5.0 μm, and the total number of S-containing phase particles with a major axis of 5.0 μm or more are respectively calculated based on the total area (mm 2 ) to obtain the number density (pieces / mm 2 ) is calculated. This number density calculation operation is performed for three or more non-overlapping measurement regions. The arithmetic mean value is calculated for the number density values of S-containing phase particles with a major axis of 2.0 μm or more and less than 5.0 μm obtained in each measurement region, and this is used as the number density of S-containing phase particles with a major axis of 2.0 μm or more and less than 5.0 μm in the sheet material. Similarly, the arithmetic mean value is calculated for the number density values of S-containing phase particles with a major axis of 5.0 μm or more obtained in each measurement region, and this is used as the number density of S-containing phase particles with a major axis of 5.0 μm or more in the sheet material. The measurement of the major axis of each S-containing phase particle and the counting of the number of particles can be performed using image processing software (e.g., ImageJ).
[0029] [Tensile strength / conductivity] The strength level required for copper alloy sheets used in current-carrying parts such as connectors and heat-dissipating parts of electronic devices varies depending on the application, and excessive strength increases the manufacturing load of parts and leads to increased manufacturing costs. The invention of Patent Document 5, which improves press-punchability by using Mg-S particles, targets high-strength sheets with a tensile strength of 900 MPa or more in the rolling direction. In the present invention, it is possible to improve the press-punchability even in Cu-[Ni,Co]-Si copper alloy sheets with a moderate strength level of tensile strength in the rolling direction, for example, 500 MPa or more and less than 900 MPa, and good bending workability is also ensured. At the same time, electrical conductivity of 40% IACS or more is obtained. The electrical conductivity of the copper alloy sheets according to the present invention is usually in the range of 70% IACS or less.
[0030] Ni, Co, and Si increase the strength of the copper alloy sheet material through the formation of precipitates. Mg and S also have a factor of increasing the strength of the copper alloy sheet material through the formation of Mg-S-based particles. In addition, in the manufacturing method of the copper alloy sheet material of the present invention described later, the amount of precipitates generated can be adjusted by the time of aging treatment, and further, the strength of the final sheet material can be adjusted by the total rolling ratio of the finish cold rolling. In the present invention, by appropriately combining these elemental technologies that affect strength, a moderate strength level of 500 MPa or more and less than 900 MPa is achieved while sufficiently securing the number density of S-containing phase particles with a major axis of 2.0 μm or more and less than 5.0 μm.
[0031] [Bending workability] Bending is often performed when processing into current-carrying parts and the like. Considering the uses of Cu-[Ni,Co]-Si-based copper alloy sheet materials, in order to obtain high reliability when processing into current-carrying parts and heat-dissipating parts, it is desirable for the sheet material to have bending workability in which the ratio MBR / t of the minimum bending radius MBR at which cracks do not occur to the sheet thickness t is 2.5 or less, as determined by a W-bend test at BW according to the technical standard JCBA T307:2007 of the Japan Copper and Brass Association. It is more preferable that the MBR / t at BW is 2.0 or less, and even more preferable that it is 1.5 or less. It is also possible to obtain a sheet with an MBR / t at BW of 0.0 (no cracks occurring in tight bending). BW (Bad Way) means that the bending axis is parallel to the rolling direction.
[0032] In addition, JCBA T307:2007 states that "This standard applies to the evaluation of bending workability of copper and copper alloy thin plate strips with a thickness of 0.1 mm or more and 0.8 mm or less." According to the study by the inventors, it was confirmed that the bending workability can be evaluated by the W-bend test method described in the standard even for Cu-[Ni,Co]-Si-based copper alloy sheets with a thickness of less than 0.1 mm. Therefore, in the present invention, the W-bend test method in BW shown in JCBA T307:2007 is extended to the case of a sheet thickness of less than 0.1 mm (for example, 0.02 mm or more and less than 0.1 mm) and is applied as it is.
[0033] [Fatigue properties] Since current-carrying parts such as connectors may be subjected to repeated stress, the use of sheet materials with good fatigue properties is advantageous in improving the reliability of the parts. It was found that in Cu-[Ni,Co]-Si copper alloy sheet materials with dispersed S-containing phase particles, good fatigue properties can be obtained when the total Ni and Co content and the Si content are adjusted to the appropriate ranges mentioned above to fully exert precipitation strengthening, and the number density of the coarse S-containing phase particles is controlled to a low value. Considering the applications of Cu-[Ni,Co]-Si copper alloy sheet materials, in a reversed-swing fatigue test using a cantilever resonance method with a test piece whose longitudinal direction is perpendicular to the rolling direction (TD), the fatigue limit at a load stress of 300 MPa was 1.0×10 6It is desirable for the fatigue life to be at least 1 million cycles. The "fatigue" state can be determined by monitoring the decrease in resonance frequency associated with the decrease in Young's modulus.
[0034] [Manufacturing method] The copper alloy sheet material described above can be manufactured, for example, by the following manufacturing process. Casting → Hot rolling → First intermediate cold rolling → Intermediate annealing → Final intermediate cold rolling → Solution treatment → Aging treatment → Finish cold rolling → Finish heat treatment Although not described in the above steps, facing is performed as necessary after the hot working, and pickling, polishing, or further degreasing is performed as necessary after each heat treatment. Each of the above steps will be described below.
[0035] [casting] The molten copper alloy having the above-mentioned chemical composition at 1180 to 1420°C is poured into a mold and cast. It is desirable to hold the molten copper alloy in the above-mentioned temperature range for, for example, about 2 to 8 hours before casting. If the temperature of the molten copper alloy before casting falls below 1180°C, a large amount of coarse S-containing phases (phases of simple S or S compounds) are likely to be generated in the cast piece, which causes deterioration of bending workability and fatigue properties. In order to homogenize the molten copper alloy, it is advantageous to increase the temperature of the molten copper alloy before casting, but if the temperature is too high, it becomes uneconomical, so it is preferable to keep the temperature in the range of 1420°C or less. As a casting method, general methods such as continuous casting, semi-continuous casting, and ingot casting can be applied, but in the present invention, control of the cooling rate is important. Specifically, the molten copper alloy at the above-mentioned temperature is poured into a mold and solidified, and then cooled under conditions where the average cooling rate from 1100°C to 600°C is 65°C / s or more. Therefore, casting equipment with sufficient cooling capacity is used. If the average cooling rate from 1100°C to 600°C is less than 65°C / s, a large amount of coarse S-containing phases is likely to be generated in the resulting slab, which causes deterioration of bending workability and fatigue properties. Note that an excessively high cooling rate increases the burden on the equipment and is uneconomical. It is preferable to adjust the average cooling rate from 1100°C to 600°C to a range of, for example, 230°C / s or less.
[0036] In the production of copper alloys, S is generally treated as an impurity, and the raw materials and refining methods are usually controlled to reduce the S content as much as possible. In contrast, in the present invention, it is necessary to strictly control the S content so that the S content in the copper alloy is within the above-mentioned predetermined content range. For example, a Cu-S master alloy prepared in advance can be used to add S.
[0037] [Hot rolling] The slab is heated to 880 to 1100°C, and then hot-rolled to a total rolling ratio of 85% or more to obtain a hot-rolled sheet. From the viewpoint of promoting homogenization of the structure, the heating temperature of the slab is more preferably 950 to 1100°C. The heating holding time of the slab is preferably set in the range of 0.5 to 12 hours. In order to obtain a desired metal structure in which S-containing phase particles are dispersed, it is effective to break up the coarse S-containing phase in the hot rolling process. For this purpose, the total rolling ratio in the hot rolling is set to 85% or more. The upper limit of the total rolling ratio in the hot rolling can be set according to the capacity of the hot rolling mill. Usually, it may be set in the range of 95% or less.
[0038] [First intermediate cold rolling, intermediate annealing, final intermediate cold rolling] In the present invention, a process of performing multiple cold rolling with intermediate annealing between them is adopted before the solution treatment. The first cold rolling performed after the hot rolling is called the "first intermediate cold rolling", and the last cold rolling performed before the solution treatment is called the "final intermediate cold rolling". The first intermediate cold rolling should preferably have a total rolling reduction of 60% or more. The final intermediate cold rolling should preferably have a total rolling reduction of 75% or more in order to introduce strain that promotes recrystallization in the subsequent solution treatment. The upper limit of the total rolling reduction for each of these cold rolling processes can be set according to the capacity of the rolling mill. It is usually sufficient to set it in the range of 99% or less. The intermediate annealing between the first intermediate cold rolling and the final intermediate cold rolling is performed at 430-620°C for 0.1-20 hours. If the temperature is too low or the holding time is too short, the removal of strain is insufficient, which may cause problems such as cracking during the subsequent cold rolling. If the temperature is too high or the holding time is too long, the material strength decreases. If necessary, one or more steps of intermediate cold rolling and intermediate annealing may be inserted between the intermediate annealing and the final intermediate cold rolling. In this case, the intermediate annealing may be performed under the same conditions as the intermediate treatment, and the intermediate cold rolling may be performed under the same conditions as the first intermediate cold rolling.
[0039] [Solution treatment, aging treatment] Next, solution treatment is performed by holding at 800 to 1,020°C for 10 to 600 seconds, and then aging treatment is performed by holding at 400 to 550°C for 1 to 24 hours.
[0040] [Finish cold rolling, finish heat treatment] After the aging treatment, a finish cold rolling is performed under the condition of a total rolling reduction ratio of 10 to 80%. Then, a finish heat treatment is performed for the purpose of reducing residual stress, improving bending workability, and improving stress relaxation resistance by reducing voids and dislocations on the slip surface. The conditions of the finish heat treatment may be heating conditions that do not cause recrystallization within a holding temperature range of 140 to 500°C and a holding time range of 5 to 3600 seconds. The final plate thickness may be, for example, in the range of 0.02 to 0.40 mm.
[0041] [Electrically conductive and heat dissipating parts] The Cu-[Ni,Co]-Si-based copper alloy sheet material obtained in the above-mentioned manner has excellent press punching properties and good bending workability, and can be adjusted to a moderate strength level, so that it can be processed into current-carrying parts such as connectors and heat-dissipating parts for electronic devices through a processing process that improves the life of dies and reduces manufacturing costs by avoiding excessive manufacturing load. In addition, the obtained parts also have good fatigue properties. EXAMPLES
[0042] Copper alloys with the chemical compositions shown in Tables 1 to 4 were melted and cast using a vertical semi-continuous casting machine. The gas phase space in contact with the molten metal during casting was air. A Cu-20.1 mass% S alloy was used to add S. The molten metal temperature before casting and the time the molten metal was held at that temperature are shown in Tables 1 to 4. The slab temperature during cooling was monitored by placing a thermocouple in the mold and incorporating the thermocouple into the slab that solidified after pouring the molten metal, and the average cooling rate from 1100°C to 600°C was determined. The cooling rate of the slab was controlled by the amount of water used to cool the mold and the amount of water used to cool the slab that came out of the mold. The analysis samples taken from the slabs were analyzed for the elements shown in Tables 1 to 4 by the method described in the above section "Example of the method for quantifying alloying elements."
[0043] The obtained slabs were held at the temperatures shown in Tables 1 to 4 for 1 to 10 hours, then removed from the furnace and hot-rolled to the total reduction ratios shown in Tables 1 to 4. After hot rolling, the oxide layer on the surface was removed (face milled) by mechanical polishing. Then, except for some examples (Nos. 51 and 54), first intermediate cold rolling, intermediate annealing, final intermediate cold rolling, solution treatment, aging treatment, finish cold rolling, and finish heat treatment were performed in the above order under the conditions shown in Tables 1 to 4. Intermediate annealing and final intermediate cold rolling were omitted in Nos. 51 and 54. The values of the total rolling ratios (%) in each rolling process shown in the tables are rounded off to the nearest whole number. The plate material obtained by the finish heat treatment in each case was used as the test material for the following investigation. The plate thickness of the test material in each case was 0.2 mm.
[0044] (S-containing phase particle number density) According to the above-mentioned "Method for measuring the number density of S-containing phase particles", the test surface parallel to the plate surface of the test material was observed with an FE-SEM (JSM-7200F manufactured by JEOL Ltd.) equipped with an EDX device, and the S-containing phase particles were confirmed by EDX analysis and secondary electron images were taken. The sample surface was prepared by mechanical polishing using abrasive paper with abrasive stone size #1000, followed by electrolytic polishing. Electrolytic polishing was carried out at 15 V for 20 seconds. Each measurement area was a rectangular area of 300 μm × 400 μm, and measurements were taken in three non-overlapping measurement areas. The total area of the measurement areas was 0.36 mm 2 The measurement of the major axis of the S-containing phase particles and the counting of the number of particles whose major axis was within a specified range were performed using the image analysis software ImageJ (National Institutes of Health (NIH), Version 1.52a) in the following manner.
[0045] First, in the secondary electron image, particles that were determined not to be S-containing phase particles were painted black. The analysis conditions for the above software were as follows: select Analyze, then Set Scale, and on the "Set Scale" screen that appears, measure the number of pixels of the scale bar length of the captured FE-SEM image and enter it in Distance in pixels. Next, enter the length of the scale bar (μm) in Known distance, set Pixel aspect ratio to 1.0, and Unit of length to μm, so that the size of the precipitates can be recognized on the software. After that, on the "Resize Image Canvas" screen, set Width to 1280 pixels, Height to 950 pixels, and Position to Top-Center, and display the image of the FE-SEM image portion excluding the scale bar portion. After setting this scale and deleting the scale bar display portion, the brightness was inverted on the "Threshold" screen, which can be displayed by successively selecting Image, Adjust, and Threshold, so that the lowest brightness pixel among all pixels had a brightness of 255 and the highest brightness pixel had a brightness of 0, and the threshold was set to a value that would make the proportion of pixels below that value closest to 5% of all pixels, thereby binarizing and identifying the areas where precipitate particles exist. After that, on the "Analyze Particles" screen of the same software, the area of one independent precipitate region was set to 0.1 μm 2 Size was set to "0.10-Infinity" as a condition for excluding particles with a major axis smaller than 2.0 μm. Furthermore, Circularity was set to 0.00-1.00, and the Fit Ellipse item was checked on the "Set Measurements" screen. Particle analysis was performed to determine the number of S-containing phase particles with a major axis (displayed as the Major item name) of 2.0 μm or more and less than 5.0 μm, and the number of S-containing phase particles with a major axis of 5.0 μm or more in the field of view.
[0046] (conductivity) The electrical conductivity of each test material was measured by the double bridge, average cross-sectional area method in accordance with JIS H0505. Considering the electrical conductivity required for current-carrying parts such as small connectors, materials with electrical conductivity of 40% IACS or more were judged to pass.
[0047] (Tensile strength) Tensile test pieces (JIS No. 5) were taken from each test material in the rolling direction, and tensile tests were conducted in accordance with JIS Z2241 with n=3 tests to measure tensile strength. The average value of n=3 was used as the performance value for the test material. From the viewpoint of ensuring bending workability and high reliability in current-carrying parts such as connectors, those with a tensile strength in the rolling direction of 500 MPa or more and less than 900 MPa were judged to pass.
[0048] (Bending workability) In accordance with the Japan Copper and Brass Association technical standard JCBA T307:2007, the ratio MBR / t of the minimum bending radius MBR at which cracks do not occur and the plate thickness t was obtained by a W-bend test at BW. The test piece size was 30 mm in the direction perpendicular to the rolling on the plate surface and 10 mm in the rolling direction (the width of the test piece). The presence or absence of cracks on the surface of the bent part was judged according to JCBA T307:2007. For samples judged to have "large wrinkles" in the appearance observation of the surface of the bent part, a specimen was prepared by cutting the deepest wrinkle part perpendicular to the bending axis direction, and the polished cross section was observed with an optical microscope to check whether cracks had occurred that progressed into the plate thickness. If no cracks had occurred, it was judged to be "no cracks observed". Considering the use of the material of the present invention, those with an MBR / t of 2.5 or less in this test were judged to pass.
[0049] (Press punching ability) A test was conducted to punch out a 5mm x 5mm square test piece using a press die for a test material with a thickness of 0.2mm. The clearance was set to two levels, 5% and 10% of the plate thickness. The square test piece was punched out so that two of the four cut edges (end faces) formed on the square test piece were perpendicular to the rolling direction. Figure 1 shows the shape of the cut edge of the punched test piece. The size of the burrs is exaggerated. For the cut edges parallel to the rolling direction of the test piece, the surface height when the cut edge is viewed in the normal direction (in this case, the direction perpendicular to the rolling direction and plate thickness direction) was measured on a line along the entire length in the plate thickness direction (punch axial direction), and a profile of the surface unevenness was created. From the profile, the length of the shear surface shown by symbol A in Figure 1 was determined, and the ratio of the shear surface to the shear surface and fracture surface was calculated. For the sake of convenience, the length including the burr portion indicated by symbol B in Figure 1 was considered to be the length of the fracture surface, and the "shear surface ratio" was calculated by the following formula (2). In this press punching test, the height of the burr is usually less than 1 μm, so including the burr in the length of the fracture surface does not interfere with the evaluation of press punchability. Shear surface ratio (%) = 100 × A / (A+B) …(2) This measurement was performed at 10 points on the cut surface (end face) parallel to the rolling direction of the test piece, and the shear surface ratio was calculated at each point using formula (2), and the arithmetic mean value was adopted as the shear surface ratio of the test material. In this test, if the shear surface ratio at 5% clearance is 40% or less and the shear surface ratio at 10% clearance is 30% or less, it can be judged that a significant improvement in press punchability is observed compared to conventional Cu-[Ni,Co]-Si-based copper alloy sheet materials. Therefore, those with a shear surface ratio of 40% or less at 5% clearance and a shear surface ratio of 30% or less at 10% clearance were judged to pass.
[0050] (Fatigue properties) Test pieces 3 mm wide and 20 mm long, with the width direction in the rolling direction (LD) and the length direction in the direction perpendicular to the rolling direction (TD), were cut out from the test material, and a reverse-swing fatigue test was carried out using the cantilever resonance method with a fatigue testing device (Nippon Technoplus Co., Ltd., RF-RT) at a load stress of 300 MPa. The change in resonance frequency was monitored during the test, and the number of cycles at which the resonance frequency reached 98% of the initial value was taken as the fatigue limit of the test piece. This procedure was carried out for five test pieces made from one test material, and the average value of the fatigue limits was adopted as the fatigue limit of the test material. If this fatigue limit was 10 6 cycle or more was judged to be acceptable. The results are shown in Tables 1 to 4.
[0051] [Table 1]
[0052] [Table 2]
[0053] [Table 3]
[0054] [Table 4]
[0055] In the test materials of the present invention, in which a predetermined amount of S was contained and the number density of the S-containing phase particles with a major axis of 2.0 μm or more and less than 5.0 μm and the number density of the S-containing phase particles with a major axis of 5.0 μm or more were controlled within the above-mentioned appropriate range, a significant improvement in press punchability was achieved while maintaining good bending workability, and good fatigue properties were achieved at a moderate strength level (tensile strength in the rolling direction of 500 MPa or more and less than 900 MPa). The electrical conductivity was also good at 40% IACS or more.
[0056] In contrast, in the comparative example No. 41, the number density of S-containing phase particles having a major axis of 5.0 μm or more could not be sufficiently reduced due to the high S content, and the bending workability and fatigue properties were poor. In Nos. 42, 43, 44, 45, 46, 51, 52, 53, 54, and 55, the number density of S-containing phase particles with major axes of 2.0 μm or more and less than 5.0 μm was low due to the low S content, and the improvement in press punchability was insufficient. Of these, in Nos. 45 and 53, the total content of Ni and Co was high, so the strength level was high and the bending workability and electrical conductivity were also poor. In No. 47, the cooling rate during casting was slow, which resulted in a high density of S-containing phase particles with a major axis of 5.0 μm or more, and the bending workability and fatigue properties were poor. In No. 48, the molten metal temperature during casting was low, so S did not dissolve sufficiently, resulting in a high number density of S-containing phase particles with a major axis of 5.0 μm or more, and poor bending workability and fatigue properties. In No. 49, the total content of Ni and Co was low, which resulted in insufficient precipitation strengthening, resulting in a low strength level and poor fatigue properties. In No. 50, the low Si content resulted in insufficient precipitation strengthening, resulting in a low strength level and poor fatigue properties.
Claims
1. The alloy has a chemical composition, in mass%, of Ni and Co: 1.00 to 3.60%, Si: 0.20 to 2.00%, S: 0.005 to 0.10%, Ag: 0 to 1.00%, Al: 0 to 3.00%, B: 0 to 0.50%, Cr: 0 to 1.00%, Fe: 0 to 3.00%, Mg: 0 to 1.50%, Mn: 0 to 1.50%, P: 0 to 0.50%, Sn: 0 to 3.00%, Ti: 0 to 1.00%, Zn: 0 to 3.00%, Zr: 0 to 1.00%, with the balance being Cu and unavoidable impurities, and has a number density of S-containing phase particles having a major axis of 2.0 μm or more and less than 5.0 μm of 50 particles / mm 2 or more, and the number density of S-containing phase particles having a major axis of 5.0 μm or more is 50 particles / mm 2 The copper alloy sheet material is as follows:
2. 2. The copper alloy sheet according to claim 1, wherein the total content of Ag, Al, B, Cr, Fe, Mg, Mn, P, Sn, Ti, Zn, and Zr is 4.00 mass% or less.
3. The copper alloy sheet material according to claim 1, wherein the Ni content is 0.80 to 3.50 mass%.
4. The copper alloy sheet material according to claim 1, having a tensile strength in the rolling direction of 500 MPa or more and less than 900 MPa.
5. 2. The copper alloy sheet material according to claim 1, having an electrical conductivity of 40% IACS or more.
6. 2. The copper alloy sheet material according to claim 1, wherein a ratio MBR / t of a minimum bending radius MBR at which cracks do not occur to a sheet thickness t in a 90° W bending test at B.W. in accordance with Japan Copper and Brass Association technical standard JCBA T307:2007 is 2.5 or less.
7. In a reverse fatigue test using a cantilever resonance method with a test piece whose longitudinal direction is perpendicular to the rolling direction, the fatigue limit at a load stress of 300 MPa was 10 6 The copper alloy sheet material according to claim 1, wherein the copper alloy sheet material has a temperature of 1000° C. or more.
8. An electric current-carrying part using the copper alloy sheet material according to any one of claims 1 to 7 as a material.
9. A heat dissipation part using the copper alloy sheet material according to any one of claims 1 to 7 as a material.
Citation Information
Patent Citations
Wrought copper alloy, copper alloy part, and process for producing wrought copper alloy
JP2011231394A
Copper alloy ingot and copper alloy material excellent in cutting workability, and copper alloy parts using the same
JP2012046812A
Copper alloy material and production method of the same
JP2021138998A
Cu-[Ni, Co]-Si-BASED COPPER ALLOY SHEET, MANUFACTURING METHOD THEREOF, ENERGIZING COMPONENT AND HEAT DISSIPATION COMPONENT
JP2023100244A
Copper-alloy material
JP2011117034A